Выражение: 1)(x-2)(x^2+2x++x)(x^2-x+1) 2)(x-3)(x^2+3x+9)-x(x+1)(x-1)

aslan2002761 aslan2002761    3   23.08.2019 02:50    0

Ответы
Dhffhjh Dhffhjh  09.08.2020 17:25
a³-+b³=(a-+b)(a²+-ab+b²)
a²-b²=(a-b)(a+b)
1)(x-2)(x^2+2x+4)-(1+x)(x^2-x+1) = x³-2³ - (x³+1³)=x³-8-x³-1=-9
2)(x-3)(x^2+3x+9)-x(x+1)(x-1)= x³-3³ -x(x²-1)= x³-27 -x³ + x =x-27
ПОКАЗАТЬ ОТВЕТЫ
sashaStreet1 sashaStreet1  09.08.2020 17:25
ответ ответ ответ ответ ответ
Выражение: 1)(x-2)(x^2+2x++x)(x^2-x+1) 2)(x-3)(x^2+3x+9)-x(x+1)(x-1)
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра